2017
DOI: 10.3233/nre-171465
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the gait speed with the quality of life and the quality of life classified according to speed-based community ambulation in Thai stroke survivors

Abstract: The gait speed was significantly correlated with the physical domains of the QOL in stroke patients. The community ambulators had the highest QOL among the three groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 34 publications
0
26
0
5
Order By: Relevance
“…Regaining walking ability is a major objective of rehabilitation 42 ; and the maximum walking speed, which was the primary outcome parameter in this study, represents the level of impairment in walking ability 43 and affects quality of life. 44,45 In this study, the mean change in walking speed created by the SMA was 9.51 cm/s (95% confidence interval, 5.66-13.35 cm/s); therefore, it was smaller than the generally regarded minimum clinically important difference of 13 cm/s for the comfortable walking speed of stroke patients. 21 It has been noted that the effectiveness of RAGT may increase with longer periods and higher movement intensities.…”
Section: Discussionmentioning
confidence: 56%
“…Regaining walking ability is a major objective of rehabilitation 42 ; and the maximum walking speed, which was the primary outcome parameter in this study, represents the level of impairment in walking ability 43 and affects quality of life. 44,45 In this study, the mean change in walking speed created by the SMA was 9.51 cm/s (95% confidence interval, 5.66-13.35 cm/s); therefore, it was smaller than the generally regarded minimum clinically important difference of 13 cm/s for the comfortable walking speed of stroke patients. 21 It has been noted that the effectiveness of RAGT may increase with longer periods and higher movement intensities.…”
Section: Discussionmentioning
confidence: 56%
“…Another limitation is that we did not examine the duration of the beneficial effects of IC following the final testing session. As we show, IC improves gait speed, so it will be important to determine whether this improvement in walking function is sustained in the long term as gait speed dramatically affects both functional indoor and outdoor ambulation and strongly correlates with quality of life after stroke (31,33,45,49). Sustained improvements in walking speed with a concordant reduction in neuromuscular fatigability would also likely increase physical fitness, which is dramatically reduced in stroke survivors (3,4), and reduce the incidence of recurrent stroke.…”
Section: Study Limitations and Future Directionsmentioning
confidence: 85%
“…In the previous research, walking speed has been reported to be correlated with the severity of patients' paralysis, sensory disturbance, and activities of daily living [21][22][23] . In this study, the walking speed is also significantly correlated with the outcomes of the BRS, SIAS, and FIM measures, supporting the results of previous studies.…”
Section: Discussionmentioning
confidence: 97%